The Relationship between Diabetic Retinopathy Degree with Visual Acuity and Retinal Nerve Fiber Layer Thickness in Type 2 Diabetes Mellitus Patients - Felanda Ahsanu Nadia; Masitha Dewi Sari (Sumatera Medical Journal, 2022)
Introduction: Diabetic retinopathy is an ocular complication of diabetes mellitus (DM), and is one of the leading causes of visual impairment and blindness worldwide.. More than one third of people with diabetes have signs of diabetic retinopathy. Methods: This was an analytic observational study with cross-sectional design. The sample was type 2 diabetes mellitus patients with diabetic retinopathy who visited the eye clinic at the University of Sumatera Utara General Hospital from September 2021-December 2021. The sample were then analyzed with the Mann-Whitney and Kruskal Wallis test to find the relationship between diabetic retinopathy degree with visual acuity and retinal nerve fiber layer thickness in type 2 diabetes mellitus patients. Results: The sample of this study were 20 subjects with diabetic retinopathy and 20 subjects without diabetic retinopathy as the control group. The mean visual acuity in subjects with mild diabetic retinopathy was 0.65+0.48. Average visual acuity in subjects with the degree of moderate diabetic retinopathy was 0.83+0.46. The mean visual acuity in subjects with a proliferative degrees diabetic retinopathy was 0.77+0.64. Mann Whitney test revealed no statistically significant relationship between the degree of diabetic retinopathy and visual acuity (p=0.734). Using the Kruskal Wallis test revealed that there was no significant relationship between the degree of retinopathy diabetic with Avg RNFL (p=0.495), superior RNFL (p=0.385), inferior RNFL (p=0.111), temporal RNFL (p=0.064), nasal RNFL (p=0.535). Discussion: Controlling blood glucose levels becomes more important than the duration of diabetes in preventing the development of retinopathy. Most patients are advised to have an HbA1c of 7% or lower, and for certain patients it is recommended to be lower than6.5%. Diabetic retinopathy slowly damages the retinal blood vessels or the optic nerve layer, leading to leakage, thus resulting in accumulation of fluid containing lipid and blood in the retina which will gradually lead to visual impairment, and even blindness. Conclusion: There is no significant relationship between diabetic retinopathy degree with visual acuity and retinal nerve fiber layer thickness in type 2 diabetes mellitus patients.